Hypoparathyroidism: Early Detection and Diagnosis Approaches - Rizqina Alya Shafa (Jurnal Biologi Tropis, 2023)
Hypoparathyroidism is an endocrine disorder characterized by low or absent production of parathyroid hormone (PTH). The most common cause of hypoparathyroidism is injury to the parathyroid glands or unintentional removal during thyroid surgery. The author aims to explore further the early detection and diagnostic approaches for hypoparathyroidism. The search was conducted through the Pubmed database using the keywords "Detection AND Diagnose AND Hypoparathyroidism." A total of 183 results were obtained. However, after applying inclusion and exclusion criteria, 7 publications were used in this literature review. The diagnosis of hypoparathyroidism is established through the assessment of clinical symptoms, physical examination, and laboratory tests.